A STUDY ON THE PREVALENCE OF SALMONELLA SPP. IN ICE CREAM MARKETED IN THRISSUR CITY - K. Radha; V. Jinitha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was carried out to check the prevalence of Salmonella spp. in ice cream marketed in Thrissur city, Kerala. Altogether 80 ice cream samples belonging to 10 different brands were randomly collected from different retail outlets of the city and were analysed for total viable count, coliform count and for the presence of Salmonella spp. The mean total viable count and coliform count in ice cream samples were 11.90±0.06 and 3.72±0.17 log cfu/g respectively. Thirty per cent of the ice cream samples exceeded the standards prescribed for coliform count by Food Safety and Standards Act (2006). Salmonella spp. was isolated from one of the ice cream samples. The presence of potential pathogen such as Salmonella in ice cream samples reveals the importance of strengthening the quality control measures to be followed during manufacture as well as storage and distribution of ice cream in order to reduce public health risk.